Mengapa Petani di Pulau Jawa lebih Produktif dibanding Petani di Luar Pulau Jawa? - Kadir, Kadir; Prasetyo, Octavia Rizky (Politeknik Statistika STIS, 2023)
Indonesia faces a challenge to narrow the paddy yield gap between Jawa dan outside Jawa to boost national yield. It requires an understanding of the main causes of the gap. Our study aims to estimate the paddy yield gap between paddy farmers in two regions and then decompose it to identify the main contributors in explaining the gap. We estimated that the average yield of farmers outside Java is about 32 percent lower than their counterparts in Java Island. The decomposition results pointed out that the difference in characteristics only has a small contribution to the total gap. The gap happens along the data distribution, in which the gap tends to be wider in the lower part of the distribution. Our findings indicate that the gap is mainly caused by the differences in environmental factors and their interaction with farmers' characteristics. So, it needs complex socio-ecological approaches to address.